Analysis of the Attributes That Affect the Preference of Consumers Towards Hajj and Umrah Offline Store in Bontang City - Yulanda, Nur Khabiba; Herdinata, Christian (KnE Social Sciences, 2021)
The fashion business has vastly grown and has created a high demand for some consumers in Bontang. The increased number of fashion stores has also changed some business strategies applied by B&B Collection store. One of the strategies is market development by opening a new store of Hajj and Umrah products that could create positive retribution to some of the new competitors. This is a great opportunity instead of opening clothing branch stores only. This study examined consumers’ preferences towards attributes of the Hajj and Umrah store in Bontang. The study conducted a quantitative-descriptive analysis of conjoint analysis. Previous studies and surveys stated that there are four attributes of Hajj and Umrah stores, which are customer service, the store’s facility, the store’s atmosphere, and its lighting mode. Each attribute has two levels and sixteen stimuli which were analyzed by SPSS 24. There were 100 respondents out of 177,722 people in Bontang City. Purposive sampling was applied. The consumers prefered full costumer service and a coffee shop with a developed assortment display. In addition, general lighting was highly preferred. The most critical attribute was customer service, followed by the store facility, the store atmosphere, and the lighting mode. Keywords: offline store attributes, consumers preference, conjoint analysis, Hajj and Umroh product